Novel imaging techniques for hydroxychloroquine retinopathy - Yusuf, Imran H.; Charbel Issa, Peter; Ahn, Seong Joon (Frontiers in Medicine, 2022)
Hydroxychloroquine retinopathy is an increasingly recognized cause of iatrogenic, irreversible visual impairment due to the expanding use of hydroxychloroquine in combination with improvements in disease detection following advances in retinal imaging techniques. The prevalence of disease is estimated to be greater than 5% amongst individuals who have used the drug for 5 years or more. In addition to conventional imaging modalities, such as spectral-domain optical coherence tomography (OCT) and fundus autofluorescence (FAF), novel retinal imaging techniques such as en face OCT, OCT angiography, fluorescence lifetime imaging ophthalmoscopy, quantitative autofluorescence, and retromode imaging are capable of detecting structural changes in the retina. These novel retinal imaging techniques have shown promise in detecting earlier disease than is possible with current mainstream imaging modalities. Moreover, these techniques may identify disease progression as well as enabling functional correlation. In the future, these novel imaging techniques may further reduce the risk of visual loss from hydroxychloroquine retinopathy through the earlier detection of pre-clinical disease.